Synthesis of Hydroxylated Biphenyl Derivatives Bearing an α, β‐Unsaturated Ketone as a Lead Structure for the Development of Drug Candidates against Malignant Melanoma. (21st January 2021) - Dettori, Maria Antonietta; Pisano, Marina; Rozzo, Carla; Delogu, Giovanna; Fabbri, Davide
Abstract: A small collection of C2 ‐symmetric hydroxylated biphenyl derivatives featuring an α, β‐unsaturated ketone as a lead structure was prepared, and the capacity of these compounds to act as antiproliferative agents against four human malignant melanoma cell lines was assayed. The prodrug approach was applied in order to improve the delivery of compounds into the cell by modulation of the phenolic hydroxy protecting group. The hydroxylated biphenyl structure bearing an α, β‐unsaturated ketone and a phenolic‐O‐prenylated chain was found to facilitate the delivery of the molecule and interactions with biological targets. Four compounds showed antiproliferative activity resulting in IC50 values in the range of 1.2 to 2.8 μM. Abstract : Cutaneous malignant melanoma is the most lethal form of skin cancer that arises from the uncontrolled proliferation of melanocytes. We report the preparation of a small collection of hydroxylated biphenyl derivatives that are structurally related to a class of naturally occurring compounds known for selective and effective antiproliferative activity toward malignant melanoma cells.